Pengaruh Kepemimpinan Transformasional Dan Kompensasi Terhadap Kinerja Pegawai Dengan Motivasi Kerja Sebagai Variabel Mediasi Pada Perguruan Tinggi Swasta Di Kota Makassar - Purbawati Naprilia, Tania; Nurmi; Usman; Nooraeni, Endah; Yunita, Irma; Mulyadi, Edi (Jurnal Teknologi dan Bisnis Cerdas, 2025)
This study aims to analyze the effect of transformational leadership and compensation on employee performance, with work motivation as a mediating variable, in private universities in Makassar City, Indonesia. A quantitative approach was employed using a survey method involving 257 permanent employees from six private universities in Makassar. Data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method via SmartPLS 4. The findings indicate that transformational leadership and compensation have a positive and significant effect on both work motivation and employee performance. Work motivation also has a positive effect on employee performance and partially mediates the influence of transformational leadership and compensation on employee performance. Simultaneous testing shows that the combination of transformational leadership, compensation, and work motivation explains a substantial proportion of the variance in employee performance. The results contribute theoretically by strengthening the human resource management literature, and practically by providing strategic recommendations to enhance employee performance through inspirational leadership development, fair compensation policies, and effective work motivation management.